Quarter Life Crisis: Apa penyebab dan solusinya dilihat dari Perspektif Psikologi? - Inka Sukma Melati (INNER: Journal of Psychological Research, 2024)
Quarter Life Crisis is a term for a crisis that is felt in the early adult phase where individuals feel anxious, worried, and hopeless for their future. Quarter Life Crisis emerged from the popular 2001 book Quarter Life Crisis: The Unique Challenges of Lifes in Your Twenties (Robbins & Wilner, 2001). At this time, the term Quarter Life Crisis is increasingly popular among young people who are entering the early adult phase. Individuals feel that this phenomenon really needs attention and is a great concern for adults. The purpose of this study is to provide an explanation of the Quarter Life Crisis phenomenon, which is very popular today and can provide a real picture of this phenomenon and its scope seen from a psychological perspective. Research data is collected through search engines such as Google Scholar. This article is relevant and then analyzed using hermeneutics. The findings of this study show that the Quarter Life Crisis phenomenon is caused by factors of uncertainty intolerance, poor personal growth, and family dysfunction.